Perilaku Pencarian Informasi Kesehatan tentang Stunting di Kalangan Masyarakat Pedesaan Tradisional - Nurhayati, Euis Sri; Tantowi, Lisy; Rosalini, Raisa Hashina; Nisa, Hairun (UI Scholars Hub, 2025)
Stunting remains a significant public health issue in Indonesia, particularly in traditional rural communities such as those in Village X, Leuwi Damar Subdistrict, Lebak Regency, Banten, which are widely recognized as the Outer Baduy community. This study aims to analyze information-seeking behavior related to health information on stunting by examining information needs, preferred sources, barriers encountered, and the socio-cultural context influencing such behavior. A descriptive qualitative approach was employed using Focus Group Discussions (FGDs) and semi-structured interviews involving 15 mothers with children under five as the primary participants. Data were analyzed thematically based on Wilson’s (1999) information-seeking behavior model and Savolainen’s (2018) information culture perspective. The findings indicate that (1) information needs are strongly associated with mothers’ direct experiences in dealing with children’s health problems; (2) village midwives serve as the most trusted and accessible information source; (3) limited information literacy and geographic distance are major barriers to seeking information; and (4) the acceptance of health information is shaped by trust and conformity with local cultural norms. This study recommends a community-based health communication strategy that leverages the role of healthcare workers and local community leaders as knowledge mediators. The findings enrich the discourse on information behavior by reaffirming the significance of trust and cultural aspects within traditional community contexts.